2020
DOI: 10.3390/cancers12082116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Bases of Mechanisms Accounting for Drug Resistance in Gastric Adenocarcinoma

Abstract: Gastric adenocarcinoma (GAC) is the most common histological type of gastric cancer, the fifth according to the frequency and the third among the deadliest cancers. GAC high mortality is due to a combination of factors, such as silent evolution, late clinical presentation, underlying genetic heterogeneity, and effective mechanisms of chemoresistance (MOCs) that make the available antitumor drugs scarcely useful. MOCs include reduced drug uptake (MOC-1a), enhanced drug efflux (MOC-1b), low proportion of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 203 publications
0
41
0
Order By: Relevance
“…Several resistance mechanisms against HER-2 inhibition have already been described [ 83 ]. One such mechanism is downregulation of the ERBB2 at a transcriptional level, leading to lower HER2 expression and failure of HER-2 inhibition strategies [ 84 , 85 ]. In vitro and in vivo models with gastric cancer cell lines show that the activation of several alternative pathways is an alternative mechanism for developing resistance to HER2 inhibition.…”
Section: The Role Of Liquid Biopsy In Disease Monitoringmentioning
confidence: 99%
“…Several resistance mechanisms against HER-2 inhibition have already been described [ 83 ]. One such mechanism is downregulation of the ERBB2 at a transcriptional level, leading to lower HER2 expression and failure of HER-2 inhibition strategies [ 84 , 85 ]. In vitro and in vivo models with gastric cancer cell lines show that the activation of several alternative pathways is an alternative mechanism for developing resistance to HER2 inhibition.…”
Section: The Role Of Liquid Biopsy In Disease Monitoringmentioning
confidence: 99%
“…EMT is a biological process in which epithelial cells lose their polarity and acquire mesenchymal morphology [34] . Previous studies have reported that EMT plays a critical role in chemoresistance in various cancers including GC [35] , [36] , [37] . Therefore, our current study sought to explore the relationship between EIF5A2 and EMT in 5-FU resistance of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Using this experimental strategy, it was possible to generate a karyogram and obtain molecular signatures for diffuse and intestinal GC, and their relationship with CNA-EMT genes independently of age, gender, % CC, H. pylori presence/absence, TNM, and treatment (naïve samples in our set). In addition, our genomic analysis was focused on the molecular profile of GC, particularly involving alterations of EMTgenes, given their role in cancer progression as epithelial cell transformation to mesenchymal cells is fundamental to metastasis (32) and chemoresistance (33,34). Our results coincide with those previously reported in the literature, which provides validity and robustness to our findings and allows us to report novel data or not yet explored potential diagnostic, prognostic, and treatment response markers.…”
Section: Discussionmentioning
confidence: 99%